Antigenicity and immunogenicity of unique prefusion-mimic F proteins presented on enveloped virus-like particles. Issue 44 (16th October 2019) - Kwon, Young-Man; Lee, Youri; Kim, Ki Hye; Jung, Yu Jin; Li, Zhuo; Jeeva, Subbiah; Lee, Sujin; Moore, Martin L.; Kang, Sang-Moo
Highlights: Mutations for stabilizing prefusion may be different in soluble proteins and enveloped VLP. Prefusion-stabilized F proteins on enveloped VLP induce IgG antibodies for pre-F antigens. Unique Prefusion VLP vaccines induce high neutralizing titers and effective viral clearance. Abstract: Pre-fusion stabilizing mutations (DS-Cav1) in soluble fusion (F) proteins of human respiratory syncytial virus (RSV) were previously reported. Here we investigated the antigenic and immunogenic properties of pre-fusion like RSV F proteins on enveloped virus-like particles (VLP). Additional mutations were introduced to DS-Cav1 (F-dcmTM VLP); fusion peptide deletion and cleavage mutation site 1 (F1d-dcmTM VLP) or both sites (F12d-dcmTM VLP). F1d-dcmTM VLP and F12d-dcmTM VLP displayed higher reactivity against pre-fusion specific site Ø and antigenic site I and II specific monoclonal antibodies, compared to F-dcmTM VLP with DS-Cav1 only. Mice immunized with F1d-dcmTM VLP and F12d-dcmTM VLP induced higher levels of DS-Cav1 pre-fusion specific IgG antibodies, RSV neutralizing activity titers, and effective lung viral clearance after challenge. These results suggest that cleavage site mutations and fusion peptide deletion in addition to DS-Cav1 mutations have contributed to structural stabilization of pre-fusion like F conformation on enveloped VLP, capable of inducing high levels of pre-fusion F specific and RSV neutralizing antibodies.